2017
DOI: 10.18203/2320-1770.ijrcog20172319
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of fetomaternal outcome in twin pregnancy with singleton pregnancy at tertiary care centre

Abstract: INTRODUCTIONMultiple pregnancy remains one of the highest risk situations for the mother, foetus and neonate despite recent advances in obstetrics, perinatal and neonatal care. Twin pregnancies have increased rates of obstetric and perinatal complications compared to singletons such as risk of miscarriage, pre-eclampsia, post-partum haemorrhage, preterm labour, iron and folic acid deficiency anemia, polyhydramnios, discordant foetal growth, abnormal vascular communications, foetal malformations, cord complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The corresponding incidence was reported in the study by Rami et al (2019) 47.7% in primipara and 52.3% in multipara otherwise According to study by Lata et al (2017), the incidence of twin pregnancy was 70.7% in multigravida and 29.3 % in primigravida. 18,14 The rate of cesarean section in the delivery of twin pregnancies was (54%). Chaudhary et al reported cessarian section rate of 67.4%, Mehta CV et al (2020) 63.3%, Arora et al 20.32%, Bangal et al 33%.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding incidence was reported in the study by Rami et al (2019) 47.7% in primipara and 52.3% in multipara otherwise According to study by Lata et al (2017), the incidence of twin pregnancy was 70.7% in multigravida and 29.3 % in primigravida. 18,14 The rate of cesarean section in the delivery of twin pregnancies was (54%). Chaudhary et al reported cessarian section rate of 67.4%, Mehta CV et al (2020) 63.3%, Arora et al 20.32%, Bangal et al 33%.…”
Section: Resultsmentioning
confidence: 99%
“…In India, twining occur approximately 1% of all pregnancies and has been reported to be responsible for 10% of all perinatal mortality. 5 Multifoetal gestation though accounting for only a lesser percentage of live births, are known to account for a ABSTRACT Background: Aim of the study was to find out foeto-maternal outcome of multifoetal pregnancy in relation to chorionicity and to analyse the associated risk factors. Methods: This study was a prospective observational study on multifoetal pregnancy conducted at Midnapore medical college and hospital.…”
mentioning
confidence: 99%